2018
DOI: 10.3390/f9070413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar and Sludge on Carbon Storage of Urban Green Roofs

Abstract: Green roofs can improve urban ecological conditions by mitigating the heat island effect and absorbing harmful gases. Soil additives can improve roof soil properties and promote the stability of the urban ecosystem. As soil additives, biochar and sludge are widely used in the ground, but their application on roofs is still scarce. This study examined the carbon storage potential of green roofs amended with sludge and biochar. The roof soil was composed of soil and varying proportions of the additives (0%, 5%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…As expected, this finding could be related to the higher rates of organic matter, TN, and TP in SS (Table 1). Similar results have been reported by Chen et al [69] and Carabassa et al [70], who observed that SS addition showed increases in the contents of SOC, TN, and TP, and thus positively improved the soil fertility. Sardans et al [71] pointed out that inputs of C, N, and P are the major processes that decide the stoichiometry of these nutrient elements in various ecosystems.…”
Section: Responses Of Soil Properties To Ss Applicationsupporting
confidence: 90%
“…As expected, this finding could be related to the higher rates of organic matter, TN, and TP in SS (Table 1). Similar results have been reported by Chen et al [69] and Carabassa et al [70], who observed that SS addition showed increases in the contents of SOC, TN, and TP, and thus positively improved the soil fertility. Sardans et al [71] pointed out that inputs of C, N, and P are the major processes that decide the stoichiometry of these nutrient elements in various ecosystems.…”
Section: Responses Of Soil Properties To Ss Applicationsupporting
confidence: 90%
“…The fit index of path analysis explained 49%, 51%, and 61% of the variation in water-retention capacity for the canopy, litter and soil layer, respectively (Table 4). The Figure 6 Water-retention capacity of the soil layer for different environmental gradients significant factors affecting the water retention capacity were mainly explained by path map and effect value, and the influence effect was classified as direct effect, indirect effect, and total effect (Chen et al, 2018a;Chen et al, 2018b).…”
Section: Influencing Factors Of Forest Water-retention Capacitymentioning
confidence: 99%
“…As a multivariate statistical method used to investigate the relationships among multiple factors in a natural system, the structural equation model (SEM) and its ecological application have received increasing attention in recent years [63][64][65][66][67][68][69][70][71][72][73]. An SEM was fitted by using the "lavaan" package in the R software [74][75][76].…”
Section: Evaluation Of the Structural Equation Modelmentioning
confidence: 99%